Store-operated Ca² entry (SOCE) pathways : emerging signaling concepts in human (patho)physiology - Groschner, Klaus; Graier, Wolfgang F.; Romanin, Christoph (Springer, 2017)
"This second edition of the book on Store-operated Ca2+ Entry Pathways has been updated with the newest discoveries that emerged in the field within the last five years. The crystal structure of the Ca2+ signaling core complex is described which adds to a new understanding of the molecular interactions involved. Each chapter has been revised and extended. The book retains its interdisciplinary approach and supplies biochemists, cell biologists and biophysicists as well as clinicians in immunology, neurology and cardiology with valuable information on Ca2+ signaling mechanisms, functions, dysfunctions and their consequences"--Publisher's description.
Keywords: Calcium channels.; Cellular signal transduction.; Intracellular calcium.; elektronické knihy; electronic books